Ultrasonic Studies of Molecular Interactions in Ternary Liquid Mixtures at Different Temperatures - S. V. Ranganayakulu* , Sanatana Ravi, D Suresh , B Ramaraju , M. Pradeep (International Journal of Emerging Trends in Science and Technology, 2017)
The behavior of mixture of pyridine, N- N dimethylformamide and cyclohexane as a function of temperature and composition has been investigated by measuring ultrasonic velocity in conjunction with density and viscosity at 288, 298, 308 and 318 K for frequency 2 MHz. From the velocity, density and viscosity data values, various acoustical and thermodynamics parameters namely, adiabatic compressibility (β), intermolecular free length (Lf), viscous relaxation time (τ), Gibbs’ free energy (ΔG), internal pressure (Пi) free volume (Vf) and specific acoustic impedance (Z) have been calculated. Also their excess values are calculated. All these parameters and their excess values have been discussed to throw light on intermolecular interactions between the components of ternary mixture.